Methylglyoxal and a spinal TRPA1-AC1-Epac cascade facilitate pain in the db/db mouse model of type 2 diabetes - Griggs, Ryan; Santos, Diogo F.; Laird, Don E.; Doolen, Suzanne; Donahue, Renee R.; Wessel, Caitlin R.; Fu, Weisi; Sinha, Ghanshyam P.; Wang, Pingyuan; Zhou, Jia; Brings, Sebastian; Fleming, Thomas; et al. (Neurobiology of disease, 2019)
Painful diabetic neuropathy (PDN) is a devastating neurological complication of diabetes. Methylglyoxal (MG) is a reactive metabolite whose elevation in the plasma corresponds to PDN in patients and pain-like behavior in rodent models of type 1 and type 2 diabetes. Here, we addressed the MG-related spinal mechanisms of PDN in type 2 diabetes using db/db mice, an established model of type 2 diabetes, and intrathecal injection of MG in conventional C57BL/6J mice. Administration of either a MG scavenger (GERP10) or a vector overexpressing glyoxalase 1, the catabolic enzyme for MG, attenuated heat hypersensitivity in db/db mice. In C57BL/6J mice, intrathecal administration of MG produced signs of both evoked (heat and mechanical hypersensitivity) and affective (conditioned place avoidance) pain. MG-induced Ca2+ mobilization in lamina II dorsal horn neurons of C57BL/6J mice was exacerbated in db/db, suggestive of MG-evoked central sensitization. Pharmacological and/or genetic inhibition of transient receptor potential ankyrin subtype 1 (TRPA1), adenylyl cyclase type 1 (AC1), protein kinase A (PKA), or exchange protein directly activated by cyclic adenosine monophosphate (Epac) blocked MG-evoked hypersensitivity in C57BL/6J mice. Similarly, intrathecal administration of GERP10, or inhibitors of TRPA1 (HC030031), AC1 (NB001), or Epac (HJC-0197) attenuated hypersensitivity in db/db mice. We conclude that MG and sensitization of a spinal TRPA1-AC1-Epac signaling cascade facilitate PDN in db/db mice. Our results warrant clinical investigation of MG scavengers, glyoxalase inducers, and spinally-directed pharmacological inhibitors of a MG-TRPA1-AC1-Epac pathway for the treatment of PDN in type 2 diabetes.